Effects of Combination Denosumab and High‐Dose Teriparatide Administration on Bone Microarchitecture and Estimated Strength: The DATA‐HD HR‐pQCT Study. (19th September 2020) - Ramchand, Sabashini K; David, Natalie L; Lee, Hang; Bruce, Michael; Bouxsein, Mary L; Leder, Benjamin Z; Tsai, Joy N
ABSTRACT: In postmenopausal women at high risk of fracture, we previously reported that combined denosumab and high‐dose (HD; 40 μg) teriparatide increased spine and hip bone mineral density (BMD) more than combination with standard‐dose teriparatide (SD; 20 μg). To assess the effects of these combinations on bone microarchitecture and estimated bone strength, we performed high‐resolution peripheral quantitative computed tomography (HR‐pQCT) at the distal radius and distal tibia in these women, who were randomized to receive either teriparatide 20 μg ( n = 39) or 40 μg ( n = 37) during months 0 to 9 overlapped with denosumab 60 mg s.c. given at months 3 and 9, for a 15‐month study duration. The 69 women who completed at least one study visit after baseline are included in this analysis. Over 15 months, increases in total BMD were higher in the HD‐group than the SD‐group at the distal tibia (5.3% versus 3.4%, p = 0.01) with a similar trend at the distal radius (2.6% versus 1.0%, p = 0.06). At 15 months, cortical porosity remained similar to baseline, with absolute differences of −0.1% and −0.7% at the distal tibia and −0.4% and −0.1% at the distal radius in the HD‐group and SD‐group, respectively; p = NS for all comparisons. Tibial cortical tissue mineral density increased similarly in both treatment groups (1.3% [ p < 0.0001 versus baseline] and 1.5% [ p < 0.0001 versus baseline] in the HD‐group and SD‐group, respectively; p = 0.75 for overall group difference). Improvements in trabecular microarchitecture at the distal tibia and estimated strength by micro‐finite element analysis at both sites were numerically greater in the HD‐group compared with SD‐group but not significantly so. Together, these findings suggest that short‐term treatment combining denosumab with either high‐ or standard‐dose teriparatide improves HR‐pQCT measures of bone density, microstructure, and estimated strength, with greater gains in total bone density observed in the HD‐group, which may be of benefit in postmenopausal women with severe osteoporosis. © 2020 American Society for Bone and Mineral Research (ASBMR).